2014
DOI: 10.1080/09668136.2014.899767
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Faces of Europeanisation: How Did the European Union Influence Corruption in Slovakia Before and After Accession?

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…These narratives in CEE confirm many of the earlier insights from the literature dealing with cohesion policy and corruption (e.g, Beblavy and Sičáková -Beblavá 2014;Surubaru 2016;Fazekas and Tóth 2016). To the extent that focus group participants' views can be considered as general opinion, there seems to be agreement that the development assistance provided by the EU is a good thing, but also that it is a magnet for schemes to convert public resources into private assets, or simply waste the money that 'needs to be spent', much of it through rigged public procurement processes.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These narratives in CEE confirm many of the earlier insights from the literature dealing with cohesion policy and corruption (e.g, Beblavy and Sičáková -Beblavá 2014;Surubaru 2016;Fazekas and Tóth 2016). To the extent that focus group participants' views can be considered as general opinion, there seems to be agreement that the development assistance provided by the EU is a good thing, but also that it is a magnet for schemes to convert public resources into private assets, or simply waste the money that 'needs to be spent', much of it through rigged public procurement processes.…”
Section: Resultssupporting
confidence: 83%
“…For instance, mayors' party affiliations shaped opportunities for pork-barrel politics using EU funds in Hungary (Papp 2019). Beblavy and Sičáková -Beblavá (2014) found that 'Structural Funds gradually became a symbol of corruption in the distribution of government subsidies' in Slovakia. Selection processes of EU funded projects were a hotbed of clientelism and direct political influence, for instance in the form of allocating contracts to 'opportunity networks' in Romania and Bulgaria (Surubaru 2016).…”
Section: Cohesion Policy Corruption and Popular Perceptionsmentioning
confidence: 99%
“…Despite the unique features of EU Funds that would imply they have sharply different impacts from national funds, there has been remarkably little scientific work on the question to date (Mendrinou ; Beblavy & Sičáková‐Beblavá ). There are, however, two bodies of literature that speak to this issue: the broad social science literature on aid dependence and the Europeanization literature in political science.…”
Section: Conceptual Framementioning
confidence: 99%
“…In spite of the considerable public and policy interest in corruption and risks in EU Funds spending, citizens, journalists, even public authorities need an open monitoring tool that will identify Red Flags in order to retain transparency policies, take precautionary measures and prevent these warnings from escalating into project failure [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%